Avaliação da eficiência operacional de terminais intermodais da região sudeste na cadeia logística de grãos por análise envoltória de dados - Peixoto, Maria Gabriela Mendonça (Universidade Federal de São Carlos, 2013)
The precarious nature of brazilian logistics infrastructure, technologically outdated, has been facing with a scenario marked by food global demand increase, a fact that may reflect in the country's economic development delays. Considering the important Brazil agribusiness nature and the participation in agricultural production expansion opportunities, it is necessary that national forces both public and private assess the possibility of performing logistical adjustments, so that the country can align its production capacity with the international consumption agribusiness demands In addition, it may be noted that, in 2011, logistics represented 10,6% of the national GPD (Gross Domestic Product), also considering that transport and storage stand out as factors that have an important influence over supply chains dynamics. In grain production chains, these logistics activities may involve intermodal terminals that may be suitable for storage and transhipment of these grains. The Southeast region plays an important role in grain production and handling processes in Brazil, distinguishing by its grain productivity (kg/ha) in 2011/2012 season, second only to the South in the 2010/11 season. Thus, this study aims to investigate Southeast intermodal terminals performance checking their levels of efficiency in brazilian grain harvest flow logistics operations. The research approach was defined as qualitative and quantitative or mixed with exploratory purposes. The research method was the case study (multicases) and data collection was conducted through interviews, using a structured questionnaire and nonprobability sampling, for convenience. Initially, the process was carried out to characterize the terminals, through the establishment of the frequency distribution and then, quantitative data were evaluated from Data Envelopment Analysis (DEA) technique. The application of both models of Charnes, Cooper and Rhodes (1978) constant returns to scale BCC - and Banker Charnes and Cooper (1984) variable returns to scale CCR - showed that only three (4, 7 and 11) of the twelve analyzed decision making units (or terminals), also known as DMUs, have got overall technical efficiency, ie, can use their inputs efficiently, without incurring on huge wastes. In addition, these terminals are the only ones with pure technical efficiency. On the other hand, the three inefficient DMUs (1, 2 and 12) showed pure technical efficiency, suggesting that these terminals could present presumable scale operation inefficiency, an aspect not addressed in this paper. The logistics terminals analysis allowed the understanding of the grain movement context from the brazilian intermodal transport perspective as well as iv it was possible to verify that a greater operational productivity can be obtained regarding the use of the structure and resources available.
Keywords: Logística; Grãos - armazenamento; Terminal intermodal; Transporte; Eficiência; AED (Análise Envoltória de Dados); Cadeias de grãos; Armazenagem; Logistics; Chain of grain; Intermodal; Transportation; Storage; Data envelopment analysis; Efficiency; ENGENHARIAS::ENGENHARIA DE PRODUCAO